Eight-year Continuous Tillage Practice Impacts Soil Properties and Forms of Potassium under Maize-based Cropping Systems in Inceptisols of Eastern India. Issue 5 (9th March 2022) - Kumar, Gopal; Kumari, Ragini; Shambhavi, Shweta; Kumar, Sanjay; Kumari, Priyanka; Padbhushan, Rajeev
ABSTRACT: Intensive conventional tillage practice has deteriorated soil quality and decreased potassium (K) availability in soil under maize-based growing areas in eastern India. Consequently, maize productivity has declined over the years demonstrating the need for sustainable alternatives. A field study was carried out in 2018 in the eighth year of an on-going long-term experiment initiated in the year 2011 to understand the impact of different tillage practices in maize-based cropping systems on soil properties and K dynamics in Inceptisols of eastern India. The experiment was laid out in split plot design with three levels of tillage practice as main plots: zero tillage, permanent raised bed and conventional tillage and in subplots as three different cropping systems viz . maize-maize, maize-wheat, and maize-chickpea. The result showed that under tillage practices, soil parameters were improved in zero tillage over the permanent raised bed and conventional tillage and among cropping systems, maize-chickpea had more nutrient availability in compared with maize-maize and maize-wheat. Soil organic carbon was built up by 10.2% in zero tillage over the initial soil measured at the time of the start of the experiment. The maximum content of water-soluble K, exchangeable K, and nonexchangeable K were recorded in zero tillage and maize-chickpea as compared to other tillage practices and cropping systems. Among Q/I parameters, potential buffering capacity (PBC K ) was maximum and activity ratio (AR K ) and labile K (KL ) were minimum under zero tillage and maize-chickpea cropping system than the other tillage practices and cropping systems. Therefore, zero tillage and maize-chickpea could be better practices over the other tillage practices and cropping systems for improving soil quality and K availability in soil.